Traditional symbols and social constructs in M. Irata’s Momuhuto: A literary sociology perspective - Aminudin, Muhammad Fauzan; Alade, Salman; Widyastuti, Sri Harti; Wiyatmi, Wiyatmi (NOTION: Journal of Linguistics, Literature, and Culture, 2024)
This descriptive qualitative study aims to explore the traditional symbols and social constructions of Gorontalo society as reflected in M. Irata’s short story Momuhuto. Employing literary sociology perspective, the data were elicited through key quotations within the text, analyzed through document analysis. The study highlights on how the short story reflects philosophical meanings behind traditional symbols and how social norms are depicted. The results indicate that Momuhuto presents meaningful symbols – such as purification rituals – emphasizing Gorontalo society’s dedication to preserving its traditions. Despite the influence of modernization, the traditional leaders play a significant role in maintaining cultural identity and social harmony. The study infers that Momuhuto not only preserves cultural heritage but also cultivates social awareness through literature. The study further suggests that literature generally assists preserve cultural identity in the face of social change. Future studies can explore how literary works from different cultures reflect the balance between modernization and tradition, presenting comparative views into how various societies navigate these obstacles while maintaining their heritage.